2009
DOI: 10.1063/1.3104858
|View full text |Cite
|
Sign up to set email alerts
|

Growth of deformation twins in room-temperature rolled nanocrystalline nickel

Abstract: Deformation twinning has been observed in room-temperature rolled nanocrystalline Ni. The growth of the deformation twins via the emission of partial dislocations from a grain boundary has been examined in detail. Partial dislocations on neighboring slip planes may migrate for different distances and then remain in the grain interior, leading to the formation of a steplike twin boundary ͑TB͒. With continued twin growth, the TBs become gradually distorted and lose their coherent character due to accumulated hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…However, MD simulations revealed stacking faults, and experiments revealed both stacking faults and deformation twins in nc Ni. These results were explained by the GPFEs [10] and other factors [188,247]. Specifically, after a leading partial generates a stacking fault, the nucleation and gliding barrier for the trailing partial is a function of c usf -c sf , which is large for Ni and Cu, as compared to Al.…”
Section: General Planar Fault Energy Effectmentioning
confidence: 99%
“…However, MD simulations revealed stacking faults, and experiments revealed both stacking faults and deformation twins in nc Ni. These results were explained by the GPFEs [10] and other factors [188,247]. Specifically, after a leading partial generates a stacking fault, the nucleation and gliding barrier for the trailing partial is a function of c usf -c sf , which is large for Ni and Cu, as compared to Al.…”
Section: General Planar Fault Energy Effectmentioning
confidence: 99%
“…S ince the discovery that nanomaterials have a significantly higher propensity to twin than traditional metals [1][2][3][4][5][6] , several studies have been devoted to identifying the unconventional causes for twinning in these materials [7][8][9][10][11] . Many numerical and experimental works have shown that twinning occurs via different mechanisms in nanograined (NG) materials than in coarse-grained (CG) materials.…”
mentioning
confidence: 99%
“…In general, partial dislocation mediated processes exhibit much higher activity in nc metals. Theoretical model [31] and experimental observation [32,33] show that it is energetically favorable for nc metals successively emitting dislocations from GBs. In other words, partial dislocation is more easily emitted in the low SFE metals.…”
Section: Resultsmentioning
confidence: 95%